Limited Excessive Voluntary Alcohol Drinking Leads to Liver Dysfunction in Mice. (19th January 2017) - Wegner, Scott A.; Pollard, Katherine A.; Kharazia, Viktor; Darevsky, David; Perez, Luz; Roychowdhury, Sanjoy; Xu, Allison; Ron, Dorit; Nagy, Laura E.; Hopf, Frederic Woodward
Abstract : Background: Liver damage is a serious and sometimes fatal consequence of long‐term alcohol intake, which progresses from early‐stage fatty liver (steatosis) to later‐stage steatohepatitis with inflammation and fibrosis/necrosis. However, very little is known about earlier stages of liver disruption that may occur in problem drinkers, those who drink excessively but are not dependent on alcohol. Methods: We examined how repeated binge‐like alcohol drinking in C57BL/6 mice altered liver function, as compared with a single binge‐intake session and with repeated moderate alcohol consumption. We measured a number of markers associated with early‐ and later‐stage liver disruption, including liver steatosis, measures of liver cytochrome P4502E1 (CYP2E1) and alcohol dehydrogenase (ADH), alcohol metabolism, expression of cytokine mRNA, accumulation of 4‐hydroxynonenal (4‐HNE) as an indicator of oxidative stress, and alanine transaminase/aspartate transaminase as a measure of hepatocyte injury. Results: Importantly, repeated binge‐like alcohol drinking increased triglyceride levels in the liver and plasma, and increased lipid droplets in the liver, indicators of steatosis. In contrast, a single binge‐intake session or repeated moderate alcohol consumption did not alter triglyceride levels. In addition, alcohol exposure can increase rates of alcohol metabolism through CYP2E1 and ADH, which can potentially increase oxidative stress and liver dysfunction. Intermittent, excessive alcohol intake increased liver CYP2E1 mRNA, protein, and activity, as well as ADH mRNA and activity. Furthermore, repeated, binge‐like drinking, but not a single binge or moderate drinking, increased alcohol metabolism. Finally, repeated, excessive intake transiently elevated mRNA for the proinflammatory cytokine IL‐1B and 4‐HNE levels, but did not alter markers of later‐stage liver hepatocyte injury. Conclusions: Together, we provide data suggesting that even relatively limited binge‐like alcohol drinking can lead to disruptions in liver function, which might facilitate the transition to more severe forms of liver damage. Abstract : The present study discovered that even limited voluntary binge‐like intake can damage the liver. Using different drinking models we were able to directly compare the effects of excessive versus more moderate levels of alcohol consumption. Excessive alcohol consumption produced multiple signs of liver dysfunction, including increased liver triglycerides, lipogenesis, and alcohol clearance, which were not present after moderate alcohol consumption. Importantly, our study demonstrates that even a short history of excessive drinking can result in multiple symptoms of early stage liver pathology.